FELTE-ULIS THIRD-YEAR STUDENTS’ BELIEFS AND PRACTICES OF MOTIVATIONAL STRATEGIES IN THEIR MICRO-TEACHING = NIỀM TIN VỀ CHIẾN LƯỢC TẠO ĐỘNG LỰC HỌC VÀ VIỆC THỰC HÀNH SỬ DỤNG CHIẾN LƯỢC CỦA SINH VIÊN NĂM THỨ BA TRONG GIẢNG TẬP TẠI KHOA SƯ PHẠM TIẾNG ANH, TRƯỜNG ĐẠI HỌC NGOẠI NGỮ - Lý, Hoàng Yến (2020)
L2 learners’ motivation has been voiced by many scholars to be closely related to teachers’ motivational teaching practices, yet many young teachers hardly ever employ motivational strategies in their classes. The question to answer is whether those teachers are aware of the effect of the techniques to motivate learners and practice those techniques during pre-service teacher training programs. There have been a significant body of research on this matter in the world but since there has been little research on this matter in Vietnam, this study was carried out. The study took third-year students at the Faculty of English language Teacher Education, University of Languages and International Studies as participants and employed mixed methods design to scrutinize the student teachers’ beliefs and practices about motivational strategies in their micro-teaching. Specifically, 109 student teachers were invited to participate in the research surveys using stratified and simple random sampling method. Questionnaires, classroom observations and interviews were used as data collection instruments while descriptive statistics and interpretative procedures served as the main data analysis methods.